Morphological and Functional Analysis of a Cohort of Patients Undergoing Orthotopic Ileal Neobladder. Issue 3 (July 2015) - Pirola, Giacomo Maria; Micali, Salvatore; Territo, Angelo; Sighinolfi, Maria C.; Beato, Alessandra; Bianchi, Giampaolo
Introduction: This study was conducted between January 2001 and December 2013 to evaluate patient's outcomes after radical cystectomy and orthotopic ileal neobladder from a morphological and functional point of view at a median follow-up of 2 years. Materials and Methods: A total of 48 eligible patents were included. We first report our technical modifications to Studer's neobladder. Sequently, after a medium follow-up of two years, we assessed morphology of the reservoir and voiding functionality of this patients cohort, submitting them to specific questionnaires and to uroflowmetry. Results: Early and late postoperative data are available for 36 patients. From the morphological follow-up, 2 years after surgery, six patients had hydroureteronephrosis for vescico-ureteral reflux in four cases (11% of total) and uretero-neobladder anastomosis stenosis in the other two (5.6% of total). Neobladder shape always remained spherical, with a relative right lateralization in eight cases (22.2%). Regarding the nine patients subjected to uroflowmetry, seven (77.7%) highlighted the lack of postvoid residual urine, with a maximum urinary flow rate within the normal range in six of them. Discussion: Improvements in surgical technique may help to reduce complications rate. From uroflowmetry analysis, we can observe that the mean filling pressure following surgery was relatively stable and urinary flow rate was mostly satisfactory. In patients without postvoid residual urine, all referred absence of daily incontinence and good quality of life. Conclusion: From this morpho-functional evaluation, our orthotopic Studer-modified ileal neobladder seems an ideal solution for urinary diversion, presenting functional features similar to native bladder and assuming a well-defined morphology, not changing in time.